The Possibilities of Sustainable Development Evaluation in the European Union Area - Huttmanová, Emília (European Journal of Sustainable Development, 2017)
The concept of sustainable development is considered as a multidimensional. In general, we can conclude, that sustainable development brings together economic, environmental and social dimensions. Process of these different dimensions evaluation is very complicated, as well as results interpretation and creating of the conclusions formulation useful in the management of sustainability. The main aim of this paper is to present the possibilities of sustainable development evaluation in the conditions of the European Area countries. Keywords: Sustainable development, sustainability, management of sustainability, Human development index, EU countries